Effect of different methods of soil preparation on soil moisture loss, weed growth and soil resistance to penetration - Lal, Harbans (Pesquisa Agropecuaria Brasileira, 2014)
The effect of different methods of soil preparation on soil moisture loss, weed growth and soil resistance to penetration has been quantified for the Latosols of Bebedouro experiment station of CPATSA/EMBRAPA, Petrolina, PE, Brazil. The methods studied are manual preparation, preparation by animal drawn wheeled tool carrier and tractorized implements. The drying characteristics of three fields with different soil physical properties were studied prior to conducting the experiment. The different methods of soil preparation caused the soil moisture loss differently. The plot prepared by animal drawn tool carrier retained more moisture for longer time even at deeper layers. The soil resistance to penetration on the surface increased with time with little variation at deeper layers.